PENGARUH METODE PENGERINGAN SIMPLISIA TERHADAP KAPASITAS ANTIOKSIDAN WEDANG UWUH - Dharma, Made Aditya; Nocianitri, Komang Ayu; Yusasrini, Ni Luh Ari (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 9 No 1 (2020): Jurnal ITEPADO - 10.24843/itepa.2020.v09.i01.p11, 2020)
This research aims to determine the effect of drying method the antioxidant capacity of wedang uwuh and to obtain the highest antioxidant capacity of wedang uwuh . This study was designed using a completely randomized design (CRD) with four parameters of drying methods there are sun-drying, air-drying, greenhouse and oven, which were repeated four times. Therewere many parameters analyzed in this research such as water content, antioxidant capacity, total phenol and sensoryincluding color, aroma, taste and overall acceptance. All data were statistically analyzed using ANOVA and continued with Duncan's (DMRT) (? = 5%). The results showed that the drying method had a significant effect on the water content, antioxidant capacity and total phenol of wedang uwuh , but did not significantly affect to the sensory results. Air-drying method produced wedang uwuh with the highest antioxidant capacity of 63,63 mgGAEAC/L, with a moisture content of 8,05 %, and total phenol of 23,70 mg/L where, based on color, taste, flavor and general acceptance the panelists rather like the wedang uwuh produced. Keywords : simplisia, wedang uwuh, drying, antioxidant